Real‐world effectiveness of a fractional CO2 laser with topical antifungal agents for the treatment of onychomycosis. Issue 6 (12th April 2022) - Lee, Soo Kyung; Kim, Ho Young; Lee, Jae Ho; Lee, Un Ha; Kim, Myoung Shin
Abstract: Current therapeutic agents for onychomycosis have limited efficacy or cause side effects. Recently, successful treatment using fractional CO2 lasers has been reported; however, the results are inconsistent. We analyzed the real‐world effectiveness of a Fractional CO2 laser for the treatment of Onychomycosis A single‐center retrospective chart review was conducted during January 2015–December 2018. Patients, diagnosed with onychomycosis through fungal culture and/or potassium hydroxide staining, underwent three or more fractional CO2 laser treatments and used topical antifungal agents. Treatment effects were assessed by using clinical images at 6, 12 months, and the last visit. Ninety‐six patients were included; they underwent an average of 7.7 laser treatment sessions. Finally, 15 patients (15.6%) showed complete response (100% clearing of all nails), 24 patients (25%) showed partial response, and 57 patients (59.4%) showed no response (no 100% clearing of nails among all treated toenails per patient including mild improvement or temporary cosmetic improvement). Multivariable logistic regression analysis revealed longer disease duration ( p  = 0.006, OR = 1.16 [95% CI: 1.05–1.31]), patients with diabetes ( p  = 0.021, OR = 9.82 [95% CI: 1.75–94.01]) and fewer number of laser treatment sessions ( p  = 0.001, OR = 0.76 [95% CI: 0.64–0.89]) were significantly associated with non‐response group. In conclusion, fractional CO2 laser with topical antifungal could be a safe alternative treatment in patients with onychomycosis, who are difficult to take oral antifungals.